Effect of amyloid-Β (25–35) in hyperglycemic and hyperinsulinemic rats, effects on phosphorylation and O-GlcNAcylation of tau protein. (June 2017) - Lozano, Liliana; Guevara, Jorge; Lefebvre, Tony; Ramos-Martinez, Ivan; Limón, Daniel; Díaz, Alfonso; Cerón, Eduarda; Zenteno, Edgar
Abstract: Aggregation of the amyloid beta (Aβ) peptide and hyperphosphorylation of tau protein, which are markers of Alzheimer's disease (AD), have been reported also in diabetes mellitus (DM). One regulator of tau phosphorylation is O-GlcNAcylation, whereas for hyperphosphorylation it could be GSK3beta, which is activated in hyperglycemic conditions. With this in mind, both O-GlcNAcylation and phosphorylation of tau protein were evaluated in the brain of rats with streptozotocin (STZ)-induced hyperglycemia and hyperinsulinemia and treated with the Aß25–35 peptide in the hippocampal region CA1. Weight, glycated hemoglobin, glucose, and insulin were determined. Male Wistar rats were divided in groups (N = 20): a) control, b) treated only with the Aβ25–35 peptide, c) treated with Aβ25–35 and STZ, and d) treated only with STZ. Results showed statistically significant differences in the mean weight, glucose levels, insulin concentration, and HbA1c percentage, between C- and D-treated groups and not STZ-treated A and B (P < 0.05). Interestingly, our results showed diminution of O-GlcNAcylation and increase in P-tau-Ser-396 in the hippocampal area of the Aβ25–35- and STZ-treated groups; moreover, enhanced expression of GSK3beta was observed in this last group. Our results suggest that hyperinsulinemia-Aβ25–35-hyperglycemia is relevant for the down regulation of O-GlcNAcylation and up-regulation of the glycogen synthase kinase-3 beta (GSK3beta), favoring Aβ25–35-induced neurotoxicity in the brain of rats. Highlights: The joint presence of streptozotocin and AB 25-35 exerts an additive effect. Hyperglycemia and hyperinsulinemia are associated with reduced O-GlcNacylation. Reduction of O-GlcNacylation in the group treated with streptozotocin plus AB 25-35 increased GSK3B expression. Hyperglycemia and hyperinsulinemia seem to be related to hippocampal damage and AD development.